Patient safety culture in Oman: A national study. Issue 5 (21st November 2019) - Al Nadabi, Waleed; Faisal, Muhammad; Mohammed, Mohammed Amin
Abstract: Rational, aim, and objectives: A positive patient safety culture in maternity units is linked to higher quality of care and better outcomes for mothers. However, safety culture varies across maternity units. Analyses of variation in safety culture using statistical process control (SPC) methods may help provider units to learn from each other's performance. This study aims to measure patient safety culture across maternity units in Oman using SPC methods. Methods: The 36‐item Safety Attitude Questionnaire (SAQ) was distributed to all doctors, nurses, and midwifes working in ten maternity care units in Oman's hospitals and analysed using SPC methods. The SAQ considers six domains: job satisfaction, perception of management, safety climate, stress recognition, teamwork, and work condition. Results: Of the 892 targeted participants, 735 (82%) questionnaires were returned. The overall percentage of positive safety responses in all hospitals ranged from 53% to 66%, but no hospital had the targeted response of above 75%. Job satisfaction had the highest safety score (4.10) while stress recognition was the lowest (3.17). SPC charts showed that the overall percentage of positive responses in three maternity units (H1, H7, and H10) was above and one (H4) was below the control limits that represent special cause variation that merits further investigation. Conclusion: Generally, the safety culture in maternity units in Oman is below target and suggests that considerable work is required to enhance safety culture. Several maternity units showed evidence of high/low special cause variation that may offer a useful starting point for understanding and enhancing safety culture.